Analisis Etika Deskriptif Pada Cerpen “Telunjuk” Karya Eli Rusli - rino, Jeki suga (STKIP PGRI SUMENEP, 2024)
ABSTRACT This study will analyze short stories with a descriptive ethical approach. Descriptive ethics describes the good and bad moral behavior of an action. Nowadays there are many cases of people's moral behavior that deviate from the prevailing norms. Corruption, murder, fraud and others are a form of deviant social behavior. We can learn people's behavior through literary media, one of which is short stories. Short stories are short stories that contain real people's behavior, experiences and imagination of the author. This research will describe the character's moral behavior in Eli Rusli's short story